ANÁLISIS COMPARATIVO DEL MARCO NORMATIVO DE GENERACIÓN DISTRIBUIDA DEL ECUADOR CON OTROS PAÍSES DE LA REGIÓN - CÓRDOVA HEMBA , ERICK SEBASTIÁN (2025)
This research project focuses on analyzing distributed generation (DG) regulations to enhance energy efficiency in Ecuador. A comparative study is conducted on the DG regulatory frameworks of Ecuador, Brazil, Mexico, and Chile, identifying strengths, weaknesses, and opportunities to improve Ecuadorian policies